Does a provider payment method affect membership retention in a health insurance scheme? a mixed method study of Ghana's capitation payment for primary care - Francis-Xavier; Renske van der Wal; Eric Nsiah-Boateng; Felix Ankomah Asante; Koos van der Velden; Ernst Spaan (BMC, 2018)
Abstract Background Ghana introduced a National Health Insurance Scheme (NHIS) in 2003 applying fee-for-service method for paying NHIS-credentialed health care providers. The National Health Insurance Authority (NHIA) later introduced diagnosis-related-grouping (DRG) payment to contain cost without much success. The NHIA then introduced capitation payment, a decision that attracted complaints of falling enrolment and renewal rates from stakeholders. This study was done to provide evidence on this trend to guide policy debate on the issue. Methods We applied mixed method design to the study. We did a trend analysis of NHIS membership data in Ashanti, Volta and Central regions to assess growth rate; performed independent-sample t-test to compare sample means of the three regions and analysed data from individual in-depth interviews to determine any relationship between capitation payment and subscribers' renewal decision. Results Results of new enrolment data analysis showed differences in mean growth rates between Ashanti (M = 30.15, SE 3.03) and Volta (M = 40.72, SE 3.10), p = 0.041; r = 0. 15; and between Ashanti and Central (M = 47.38, SE6.49) p = 0.043; r = 0. 42. Analysis of membership renewal data, however, showed no significant differences in mean growth rates between Ashanti (M = 65.47, SE 6.67) and Volta (M = 69.29, SE 5.04), p = 0.660; r = 0.03; and between Ashanti and Central (M = 50.51, SE 9.49), p = 0.233. Analysis of both new enrolment and renewal data also showed no significant differences in mean growth rates between Ashanti (M = − 13.76, SE 17.68) and Volta (M = 5.48, SE 5.50), p = 0.329; and between Ashanti and Central (M = − 6.47, SE 12.68), p = 0.746. However, capitation payment had some effect in Ashanti compared with Volta (r = 0. 12) and Central (r = 0. 14); but could not be sustained beyond 2012. Responses from the in-depth interviews did not also show that capitation payment is a key factor in subscribers' renewal decision. Conclusion Capitation payment had a small but unsustainable effect on membership growth rate in the Ashanti region. Factors other than capitation payment may have played a more significant role in subscribers' enrolment and renewal decisions in the Ashanti region of Ghana.